МОЖНИТЕ КРАТКИ ЛИЧНОЗАМЕНСКИ ФОРМИ ПРИ УДВОЈУВАЊЕТО НА ТРИВАЛЕНТНИТЕ ГЛАГОЛИ (Filološke studije, 2019)
In this paper, we are going to present possible short pronouns about direct and indirect objects, used together with trivalent verbs in Macedonian language.